2009
DOI: 10.1111/j.1442-9071.2009.02116.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting transconjunctival sutureless 25‐gauge vitrectomy: still worthwhile?

Abstract: To present the outcomes of various retinal conditions treated with the sutureless 25-gauge (25G) vitrectomy technique. Retrospective case review of 232 eyes of 228 patients who underwent 25G vitrectomy from January 2003 to August 2006. Follow-up was a minimum of 3 months. Indications for surgery included idiopathic macular hole, rhegmatogenous retinal detachment, epiretinal membrane and proliferative diabetic retinopathy. Main outcome measures included final visual acuity, re-operation rate and surgical compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…24,42,43,[48][49][50][51] Postoperative hypotony at any point within the first week in this series after 25-gauge PPV was seen in 5 of 54 patients (9.3%), which is consistent with the published rates of hypotony after 25-gauge PPV that range from 0% to 9.2%. 21,52,53 The overall rate of hypotony at any point in the first postoperative week in our series regardless of size of instrumentation was 9.8% (9 of 92 patients). When looking at postoperative hypotony, only 7 of 92 patients (7.6%) had this complication 2 hours postoperatively, which is slightly lower than the rate of 11.3% cited by another study.…”
Section: Discussionmentioning
confidence: 94%
“…24,42,43,[48][49][50][51] Postoperative hypotony at any point within the first week in this series after 25-gauge PPV was seen in 5 of 54 patients (9.3%), which is consistent with the published rates of hypotony after 25-gauge PPV that range from 0% to 9.2%. 21,52,53 The overall rate of hypotony at any point in the first postoperative week in our series regardless of size of instrumentation was 9.8% (9 of 92 patients). When looking at postoperative hypotony, only 7 of 92 patients (7.6%) had this complication 2 hours postoperatively, which is slightly lower than the rate of 11.3% cited by another study.…”
Section: Discussionmentioning
confidence: 94%
“…Vitrectomy combined with membrane‐peeling surgery is an effective method to manage macular membranes (Sandinha et al. ; Wei et al. ; Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al [1,2] described the use of a 25-gauge transconjunctival sutureless vitrectomy (25-G TSV) system, and found it applicable to a variety of vitreoretinal pathologies. Since that time, many investigators have reported successful results with 25-G TSV, its popularity has been rapidly increasing, and its indications continue to expand [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The sutureless nature of small-gauge vitrectomy leads to less traumatic surgical manipulation, less surgically induced astigmatism, and less postoperative patient discomfort, which facilitates early visual recovery [2][3][4][5][6][7][8]. However, this technique has been associated with a higher incidence of complications such as postoperative hypotony, choroidal detachment and endophthalmitis [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%